Characteristic external genitalia in male neonates with 5α-reductase deficiency - Takeshi Munenaga; Yosuke Ichihashi; Satsuki Nakano; Hironori Shibata; Takeshi Sato; Hiroshi Asanuma; Keiko Homma; Tomonobu Hasegawa; Tomohiro Ishii (Endocrine Journal)
There have been no reports comparing neonatal external genitalia of 5α-reductase deficiency (5αRD) with those of other 46,XY differences of sex differentiation (DSD). This study enrolled 31 Japanese cases of 46,XY DSD whose external genitalia was examined during the neonatal period; four were diagnosed as 5αRD and 15 were defined as non-5αRD by genetic analysis of SRD5A2 or urinary steroid metabolites. We compared the following characteristics between 5αRD and non-5αRD groups, adjusting the severity of undermasculinization of the external genitalia: stretched penile length (SPL), glans width, location of the external urethral opening, and proportion of undescended testis. The external genitalia of all the 5αRD cases were Quigley classification grade 2 or 3. We compared the phenotypes between the four 5αRD cases and 11 non-5αRD cases with grade 2 or 3. The median (range) of SPL in the 5αRD group (14 mm [11-16]) was significantly lower than that in the non-5αRD group (22 mm [15-29]) (p = 0.003). An SPL cut-off value of <15 mm yielded a sensitivity of 50% (95% confidence interval [CI]; 7–93%) and specificity of 100% (95% CI, 72–100%) for discriminating between the groups. The median glans width, location of the external urethral opening, and proportion of undescended testis were not significantly different between the groups. The SPL of 5αRD in Quigley classification grade 2 or 3 was significantly shorter than that of other 46,XY DSDs with the equivalent grade.